1996
DOI: 10.1046/j.1365-2265.1996.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure profiles and plasminogen activator inhibitor (PAI‐1) activity in lean women with and without the polycystic ovary syndrome

Abstract: The only measurable vascular risk factor associated with hyperinsulinaemia and menstrual disturbance in non-obese women with PCOS is an elevated plasma PAI-1 activity. These women did not differ from controls in ambulatory blood pressure profiles, lipid measurements or in a parental history of premature vascular disease. PAI-1 and plasminogen are involved in ovarian follicle maturation and the present finding suggests a biologically plausible link between hyperinsulinaemia, anovulation and vascular risk in PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
3
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 43 publications
5
86
3
11
Order By: Relevance
“…Subsequently, plasma PAI-1 levels of PCOS phenotypic group were statistically higher than those of controls Table 4 The percentages of PCOS patients and controls in genotypes 4G/4G, 4G/5G and 5G/5G. (Table 6), which is in accordance with previous studies (8,9). In this study, women with PCOS with 4G/4G genotype had higher PAI-1 levels than any other genotype in the studied groups except for 4G/4G of the control group (Table 6).…”
Section: Discussionsupporting
confidence: 80%
“…Subsequently, plasma PAI-1 levels of PCOS phenotypic group were statistically higher than those of controls Table 4 The percentages of PCOS patients and controls in genotypes 4G/4G, 4G/5G and 5G/5G. (Table 6), which is in accordance with previous studies (8,9). In this study, women with PCOS with 4G/4G genotype had higher PAI-1 levels than any other genotype in the studied groups except for 4G/4G of the control group (Table 6).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, others reported higher PAI-1 levels in normal weight women with PCOS and a correlation between PAI-1 levels and both serum insulin levels and the HOMA-IR index [13,21,22]. However, our findings do not suggest that IR modulates PAI-1 levels in normal weight women with PCOS because PAI-1 levels drogenemia in the regulation of PAI-1 levels in PCOS.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies controlling for insulin resistance have found that low high-density lipoprotein (HDL) and high triacylglycerol levels are associated with insulin resistance rather than with PCOS (10). Hypertension, furthermore, is uncommon in women with PCOS (11,12).…”
Section: Introductionmentioning
confidence: 99%